Protocol jungle hampers organic exports - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Organic farming in ACP countries is reportedly spreading fast. It fits well into farmers low input strategies and renders extra income if it can be sold as organic produce. If indeed, because, for exports to countries of the European Union,...